Pene Lando Tradition: Islamic Synchretism and Local Culture in the Pene Jerowaru Village East of Lombok - Al Idrus, S Ali Jadid (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
Religion contains of rules and teachings, which cannot be connoted as a scary thing and has no space for discussion. How if religion is faced with something that has strongly deep in a particular society or better known as customs or more space that is 'culture'. If religion and culture are clashed, it will have an impact on one of them will die and sink. But if these two things work in harmony, it will appear a new culture that issyncretism cultural. This is what happened in the Pene Jerowaru village, East Lombok. The result of syncretism (Islam and cultural customs / local wisdom) was born a tradition that is the Pene Lando tradition, which took place since KedatuanPene (Pene Kingdom). How is the developing process in the Pene village and formulated the Penelando tradition in daily life, which gave produced the 'beqen' tardition. In the Pene community life, Pene Lando tradition is a legacy that must be maintained. The 'Pene Lando' tradition, if saw from its historical traces, contains a philosophy, it does not clash with the Islamic Shari'ah which is in fact governs all aspects of the people lives.